56 The inferior vena cava – a reproducible and clinically useful tool in the monitoring and treatment of heart failure which deserves greater clinical prominence. (5th October 2017) - Barrett, M; Iacoviello, M; Monitillo, F; Grande, D; Rizzo, C; Patle, A; Fox, R; Campbell, P; O'Hanlon, R; McDonald, K
Abstract : Background/Introduction: Heart Failure (HF) management has advanced, however hospitalisation rates and mortality remain high. Maintaining euvolaemia is key to preventing decompensation but can be challenging. The Inferior Vena Cava (IVC) is a pliable reservoir for circulating volume, and changes in its shape during respiratory cycles are recognized as markers of intravascular volume status, albeit not routinely used in HF management. Purpose: To assess the reproducibility and test the clinical utility of using the IVC as a marker of volume status in a chronic HF population as well as to track change in IVC metrics in response to volume removal. Methods: This was a multicentre study conducted between St. Vincent's University Hospital (SVUH) and St. Michael's Hospital (SMH) in Dublin. Stable outpatients were enrolled in prospective fashion during routine scheduled heart failure visits to SMH. Reproducibility was measured by three repeated measurements of maximal IVC diameter (IVCd) and collapsibility index (CI) at 0, 1 and 24 hours. Recompensating HF patients were enrolled prospectively from attendances to SVUH emergency department with acute decompensated heart failure. IVC metrics after admission were followed daily for 48 hours and then at 14 days post-admission. Dialysis patients were enrolled from patients undergoing intermittent haemodialysis in SVUH for stable chronic kidney disease. IVC metrics were measured at commencement, midpoint and end of dialysis. Data collected were correlated with markers of volume overload including natriuretic peptide (BNP). Results: A total of 60 patients were included, 40 in the stable cohort and 10 each in the dialysis and recompensating arms. Serial IVC measurements over 24 hours showed good reproducibility, with an average standard deviation around the mean of 1.3 mm for IVCd and 7% for CI. When examining the stable cohort, patients with a dilated or poorly collapsible IVC had a significantly higher N-terminal pro B-type NP (3682 pg/mL vs 490 pg/mL, p=0.015) and poorer glomerular filtration rate (55 ml/kg/min vs 69 ml/kg/min p=0.029). Patients in the dialysis arm had an overall IVCd reduction of >30% over the course of their treatment which correlated with a 15% rise in haematocrit. Patients in the recompensating arm experienced a 30% reduction in IVCd during inpatient treatment over 48 hours. This subsequently rose after discharge back to similar size as their IVCd at enrollment, potentially reflecting the fact that the first month post-discharge is where rehospitalisation rates are highest. Conclusion(s): Measurement of IVC metrics appears to reflect volume status as well as matching fluid shifts in response to dialysis and diuretics. Use of the IVC to more precisely maintain euvolaemia in volume-dependent patients may deserve greater attention as a therapeutic target.